Tribe of Hackers : Cybersecurity Advice from the Best Hackers in the World - Carey, Marcus J.; Jin, Jennifer (Indianapolis, Indiana : John Wiley & Sons, Incorporated, 2019)
Tribe of Hackers: Cybersecurity Advice from the Best Hackers in the World (9781119643371) was previously published as Tribe of Hackers: Cybersecurity Advice from the Best Hackers in the World (9781793464187). While this version features a new cover design and introduction, the remaining content is the same as the prior release and should not be considered a new or updated product. Looking for real-world advice from leading cybersecurity experts' You've found your tribe. Tribe of Hackers: Cybersecurity Advice from the Best Hackers in the World is your guide to joining the ranks of hundreds of thousands of cybersecurity professionals around the world. Whether you're just joining the industry, climbing the corporate ladder, or considering consulting, Tribe of Hackers offers the practical know-how, industry perspectives, and technical insight you need to succeed in the rapidly growing information security market. This unique guide includes inspiring interviews from 70 security experts, including Lesley Carhart, Ming Chow, Bruce Potter, Robert M. Lee, and Jayson E. Street.-Get the scoop on the biggest cybersecurity myths and misconceptions about security -Learn what qualities and credentials you need to advance in the cybersecurity field -Uncover which life hacks are worth your while -Understand how social media and the Internet of Things has changed cybersecurity -Discover what it takes to make the move from the corporate world to your own cybersecurity venture -Find your favorite hackers online and continue the conversation Tribe of Hackers is a must-have resource for security professionals who are looking to advance their careers, gain a fresh perspective, and get serious about cybersecurity with thought-provoking insights from the world's most noteworthy hackers and influential security specialists.
Description based on online resource; title from digital title page (viewed on September 19, 2019).
Keywords: Computer security; Computers; Electronic books